Left atrial dysfunction relates to symptom onset in patients with heart failure and preserved left ventricular ejection fraction. (3rd September 2014) - Sanchis, Laura; Gabrielli, Luigi; Andrea, Rut; Falces, Carles; Duchateau, Nicolas; Perez-Villa, Felix; Bijnens, Bart; Sitges, Marta
Abstract: Aims: Pathophysiology of heart failure (HF) with preserved ejection fraction (HFPEF) remains unclear. Left atrial (LA) function has been related to HF symptoms. Our purpose is to analyse LA function in outpatients with new onset symptoms of HF. Methods and results: An observational study was performed including 138 consecutive outpatients with suspected HF referred to a one-stop clinic. Final diagnosis [HF with reduced EF (HFREF), HFPEF, or non-HF] was established according to current recommendations. Echocardiography was performed in all patients. LA function was analysed using strain derived from speckle tracking in sinus rhythm patients ( n = 83). Results were analysed with ANOVA and Bonferroni statistical tests. Receiver operating characteristic (ROC) curves were constructed to investigate the predictive ability of LA parameters for the final diagnosis of HF. Patients were 75 ± 9 years and 63% women. Final diagnosis was 23.2% HFREF, 45.7% HFPEF, and 31.2% non-HF. Left ventricular strain rate showed no differences between non-HF and HFPEF groups, but both groups showed differences with the HFREF group. LA strain rate (A- and S-waves) was significantly reduced in both HF groups (without differences among them) when compared with the non-HF group. LA strain rate and indexed volume showed significant accuracy for HF diagnosis in ROC curves. Conclusions: In outpatients with new-onset symptoms of HF, LA dysfunction was observed. It might be the initial mechanism in the development of symptoms in HFPEF patients. These findings support the relationship of LA dysfunction with HFPEF, suggesting that the analysis of LA function may be useful in sinus rhythm patients with new-onset dyspnoea.